DIFFERENTIAL DIAGNOSTICS OF PROSTATE TUBERCULOSIS - E. V. Brizhatyuk; V. T. Khomyakov; A. A. Baranchukova (Туберкулез и болезни лёгких)
Prostate tuberculosis is difficult to be diagnosed, especially if lesions are limited only by this organ. The article analyses the experience of differential diagnostics of prostate tuberculosis based on the data of examination of 84 patients. 45 of them were diagnosed with prostate tuberculosis, and 39 patients were diagnosed with chronic bacterial prostatitis. Pathognomonic diagnostics criteria of prostate tuberculosis were the following: detection of tuberculous mycobacteria in the prostatic fluid or ejaculate, signs of granulomatous prostatitis with areas of cavernous necrosis in prostate biopsy samples, and prostate cavities visualized by X-ray or ultrasound examinations. Should the above criteria be absent, the disease can be diagnosed based on the combination of indirect signs: symptoms of prostate inflammation with active tuberculosis of the other localization; large prostate calcification, extensive hyperechoic area of the prostate, spermatocystic lesions, leucospermia and hemospermia, failure of the adequate non-specific anti-bacterial therapy.